Students’ Perceptions of Self-Assessment in Islamic Education Learning - Khoiriyah, Niswatin; Nisak, Nur Maslikhatun; Kusaeri, Kusaeri; Niam, Khoirun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Assessment has shifted from assessment of learning to assessment for learning. Self-Assessment (SA) is generally a formative assessment practice and seems to play an important role in developing students' spiritual attitudes, including being obedient to worship, practicing Islamic teachings, and religious tolerance. This study aims to analyze students' perceptions of SA in learning Islamic Education (IE). Using experimental research, which was conducted at the Islamic Senior High School Surabaya, Indonesia in IE lessons. Data collection techniques using observation, interviews, and documentation. The population of this study is students at the Islamic Senior High School. The results of the research showed that students felt that they were able to assess their spiritual attitude and that SA helped students to learn IE, was able to increase learning motivation, students had positive experiences in implementing SA and there were great benefits from SA in developing spiritual attitudes.